Natural radon levels act as markers of hydrodynamic behavior in the mountain karst aquifer of Bossea Cave, Italy - Luca Biamino; Chiara Colombero; Adriano Fiorucci; Guido Peano; Bartolomeo Vigna (Scientific Reports)
Abstract Radon originating from meta-volcanics located at the bottom of Bossea karstic mountain aquifer is subject to transport within the cave through both advective and diffusive processes. According to the double convective cell model of circulation referable to this hypogeal atmosphere, it is possible to correlate radon fluctuations with hydrodynamics, excluding the influence of external meteo-climatic factors. Transfer of gas from underground water flows presents delayed concentration maxima compared to flood peaks, amounting to 45 h in the upper meta-carbonate canyon and 66 h in the collapse chambers located at the contact with the meta-volcanics. Furthermore, different radon concentrations in water can be detected between the main creek and secondary inflows. Although both are subjected to a piston flow hydrodynamic response, the former shows an increase in radon during floods (with a lag of 46 h) due to the mobilization of long-resident water volumes in karst fractures, while in the latter case, there is a dilution of water in contact with radioactive elements of the impermeable basement (delayed by 6 h and caused by volumes of neo-infiltration). The analysis of radon emissions related to the site seismicity reveals no relationship, likely due to the low magnitudes and the predominant effect of hydrodynamics.